Answer: 109.5
Step-by-step explanation: EACH year for three years would be 1095 if you multiply 365 (each year) by 3 (the amount of years) and then divide that by 10. Im not entirely sure but I hope I helped
Answer:
0
Step-by-step explanation:
–5(3 – q) + 4 = 5q – 11
-15 +5q + 4 = 5q -11
-11 + 5q = 5q - 11
+5q - 5q = -11 + 11
0=0
I would start by plugging in a number for x. Just any random number. Let's take 2 for example. Then the equation would go from 2x + y = -4, to 2(2) + y = -4. Then solve.
2(2) + y = -4
4 + y = -4, after you've done that, plug in a number for y, that completes the equation. In this case, the only acceptable number, would be -8. Because it completes the number sentence.
4 + (-8) = -4
-4 = -4.
Now plug in other numbers, to get the same outcome. Hope this helped!
-Twixx